Pengembangan Video Pembelajaran Teknik Dasar Bermain Biola Komunitas Musik Taman Suropati - Listiyani Siti Romlah (Universitas Negeri Jakarta, 2022)
This study aims to provide a comprehensive overview and detailed information about the process of developing video as medium of instructional to learn the basic techniques of playing violin. This study also aims to provide a new instructional media for the beginner of violin learners.The Development refers to the model of Baker and Schutz product development. In general, this development model consists of seven general steps namely: product formulation, specification of learning, item tryout, product development, product testing, product revision, analysis of operations. To support the development of this research, in the model development, used ADDIE model guidlines to compose the competence map, in the product development phase the non-linear instructional video production guidelines from Pustekkom Kemdiknas and guidlines of the Robinson Situmorang video script writing. Evaluation of the program includes three aspects; materials, media and learning which are then tested an expert in media and an expert in material, as on three students in one-to-one evaluation, ten students in small groups, and fifteen students on stage field testFrom these results it can be concluded the basic violin skill instructional video for beginner that has been developed can be categorized as a good category. The implications of this research for the beginner of violin learners at Komunitas Musik Taman Suropati is as a source of independent learning and skills to increase understanding technique. With this instructional media in instructional the violin is expected to be more effective and efficient. In addition, other media developers can also use this instructional video as motivation and as a reference in making better and qualified work.